Perancangan Komik Digital sebagai Media Informasi untuk Meningkatkan Kesadaran akan Dampak Negatif Judi Online - Raihan Rawis, Kevin; Mahardika, Ratih (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
The development of digital technology has made it easier for people to access everything. However, this can also create problems, such as the practice of online gambling. The use of online gambling has an impact on social, economic, and mental health, especially for adolescents and young adults. The purpose of this research is to design a Webtoon-based digital comic as an easily accessible and visually appealing information medium about the impact of online gambling. This research uses a mixed-method type with a design thinking approach, which has five stages: Empathize, Define, Ideate, Prototype, and Test. This data was obtained thru interviews with psychologists, administering questionnaires to 152 respondents aged 15-25, literature studies, and comic comparisons. The results show that this comic is quite effective as an information medium, with 94.4% of respondents gaining new knowledge and 80.65% considering the comic beneficial for understanding online gambling information. Further research is suggested to develop similar media with the same theme or other social issues, with better visual quality and a stronger storyline, so that the educational message is more easily accepted by all segments of society.